THE APPLICATION OF CHARACTER EDUCATION IN TEACHING ENGLISH CARRIED OUT BY STUDENTS PRACTICE FIELD EXPERIENCE OF IKIP SARASWATI TOWARD THE EIGHTH GRADE STUDENTS OF SMP N 2 TABANAN - Ni Luh Nanik Puspadi; Gusti Ayu Gede Sukraningsih; Desak Nyoman Alit Sudiarthi (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2022)
The purpose of national education contains human values utilized as the source in the development of character education which is developed at every level of education. This research is purposed to describe character education in English learning practiced by English department student of IKIP Saraswati toward the eighth grade students of SMP N 2 Tabanan. The subject of this research were two English Education Department students of IKIP Saraswati as practicing teachers and seventy students. This research was descriptive qualitative research in which the data were collected by using the techniques of observation, interview, and documentation. The data were analyzed qualitatively including data reduction, data display, conclusion, and verification. The result of this research showed that (1) Character education were implemented in the learning process including pre-activity, main activity, and post- activity by utilizing democratic method in pre activity and share search method and active student method in main and post activity; (2) The values of character applied were discipline, creative, democratic, responsibility, having good reading habit, curiosity, and communicative; (3) Several students were not creative, having good reading habit, curious, and communicative. It was caused by lack of students’ good reading habit and less attention carried out by the practicing teacher in giving apperception and raising students’ motivation. The conclusion of this research is character education is applicated quite well considering that some students were still not able to implement the character values well. Therefore, it is recommended that the practicing teacher have to carry out apperception well, increase students’ motivation, and encourage students to build and develop their good reading habit.